Organic-inorganic composite filament and method for producing the same
Patent Information
- Application Number
- CN202311817808.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-27
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-12-27
AI Technical Summary
采用磁控溅射的方法在纤维表面沉积SiO2,可以通过无机层的高模量提高PI纤维的抗压缩能力,但并未考虑表面润滑性能的提升,同时无机粒子沉积堆积缺少粘结成分,也难以有效提升纤维的耐磨性能
[0039](1)本发明创新性地开发了一种有机/无机复合纤维长丝的制备方法,利用无机物前驱体作为种子点,提高氟树脂纳米颗粒的吸附均匀度,进一步在高温处理的作用下同时完成无机物结构转化、PI结构转化,以及氟树脂熔融形成连续膜层的多层级物理、化学结构变化,利用氟树脂的熔融形成连续膜层,提高无机物与PI纤维的粘结性。
Smart Images

Figure CN117926580B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of high-performance fiber technology, specifically to a composite filament and its preparation method. Technical Background
[0002] Polyimide (hereinafter, sometimes simply referred to as PI) fiber filaments are a type of PI material used in fibrous form. They fully retain the inherent properties of PI materials, such as resistance to high and low temperatures, aging resistance, low water absorption, low dielectric constant, and high insulation. Furthermore, due to their highly oriented molecular chain structure, they possess outstanding tensile strength and modulus, making them suitable for preparing lightweight, high-strength, and microwave-transparent advanced composite materials, with broad application prospects in aerospace and other fields. However, precisely because of their highly oriented molecular chains and the covalent bonds arranged along the fiber axis, the interaction forces between molecular chains in the fiber diameter direction are relatively weak, resulting in lower tear and compressive strength, which affects the fiber's abrasion resistance and the composite material's compressive strength.
[0003] Existing technologies have been used to improve the abrasion resistance of polyimide fibers. Results show that methods such as fiber twisting or surface sizing (Lu Fan, Research on Polyimide Fiber Weaving Technology and Surface Modification, Master's Thesis, Beijing University of Chemical Technology, January 2023) can improve fiber bundleability and abrasion resistance to a certain extent. Chinese invention patent application CN201810874124.0 also discloses a method for preparing polyimide ropes with good abrasion resistance by sizing, twisting, and re-twisting single fibers into strands. The sizing agent is preferably at least one of polytetrafluoroethylene, epoxy resin 70C, and organosilicon SH3068, and the drying temperature is between 40-200℃.
[0004] Existing technologies have been researched to improve the compressive properties of PI fibers. Our team disclosed a PI fiber surface modification method in Chinese invention patent application CN202211624832.1, which uses magnetron sputtering technology to deposit SiO2 on the PI fiber surface, thereby improving the compressive strength of the PI fiber and the interfacial bonding strength with the resin. Chinese invention patent application CN202211500605.8 discloses a method for constructing an inter-molecular chain crosslinking network using polyamine compounds, improving the lateral interaction between molecular chains and thus enhancing the fiber's compressive properties.
[0005] As an organic fiber, unlike carbon fiber which has strong interlayer π-π interactions, PI fiber has weak inter-chain forces and only weak van der Waals forces between fibrils for lateral support. Therefore, its tear and compressive strength are low, which affects the wear resistance of the fiber and the compressive strength of the composite material.
[0006] Existing technologies for improving the abrasion resistance of PI fibers mainly employ methods such as fiber twisting and sizing to enhance the abrasion resistance of the fibers through improved bundle and lubricity. However, these methods have limited effectiveness and cannot simultaneously improve the compressibility of the fibers.
[0007] Existing technologies for improving the compressibility of PI fibers involve constructing cross-linking points within the PI fiber to enhance the interaction between molecular chains and improve compressibility, but they do not improve the wear resistance of PI fibers. Depositing SiO2 on the fiber surface using magnetron sputtering can improve the compressibility of PI fibers through the high modulus of the inorganic layer, but it does not consider improving surface lubrication. Furthermore, the lack of binding components in the inorganic particle deposition makes it difficult to effectively improve the wear resistance of the fibers. Summary of the Invention
[0008] In view of the shortcomings of existing technologies, such as the difficulty in simultaneously improving the compression resistance and abrasion resistance of polyimide fiber filaments, the purpose of this invention is to provide a polyimide fiber filament that can simultaneously improve compression resistance and abrasion resistance, and a method for preparing the same.
[0009] In order to achieve the purpose of this invention, the inventors conducted repeated and in-depth research and found that by using an organic / inorganic composite method to construct a shell layer composed of inorganic substances and fluororesin on the surface of polyimide fibers, forming an organic / inorganic composite fiber composed of polyimide-inorganic substances-fluororesin, it is possible to simultaneously improve the compression resistance and wear resistance, thereby completing this invention.
[0010] According to the purpose of this invention, an organic-inorganic composite filament is provided, comprising a filament and a shell layer formed on the surface of the filament. The shell layer is an organic-inorganic composite shell layer composed of inorganic materials and fluororesin, and the fluororesin forms a continuous film layer on the surface of the filament. Compared with the filament, the organic-inorganic composite filament can simultaneously improve the compression resistance and wear resistance.
[0011] Preferably, the filament is a polyimide fiber, but it is not limited thereto. High-performance fibers such as aramid fiber, aramid III fiber, PBO fiber, PBI fiber, polyarylate fiber, PTFE fiber, carbon fiber, ceramic fiber, and glass fiber can also be used to form the organic-inorganic composite fiber filament of the present invention. In the present invention, the inorganic material is preferably an inorganic oxide, such as TiO2, SiO2, ZrO2, etc., but not limited thereto, and more preferably TiO2.
[0012] According to the purpose of this invention, the present invention also provides a method for preparing organic-inorganic composite filaments, which includes the following steps:
[0013] 1) Polyamic acid is wet-spun to obtain polyamic acid filament a;
[0014] 2) Dissolve the inorganic precursor in water to obtain an inorganic precursor solution with a concentration of 0.01 mol / L-2 mol / L;
[0015] 3) Immerse the filament a obtained in step 1) into the inorganic precursor solution in step 2) for 1 min to 60 min, and then take it out to obtain polyamic acid filament b;
[0016] 4) Immerse the filament b obtained in step 3) into a fluororesin nano-dispersion solution with a concentration of 1wt%-20wt% for 1min-30min and then remove it to obtain filament c;
[0017] 5) The filament c obtained in step 4) is dried and hot drawn to obtain filament d, wherein the drying temperature is between 100-200℃ and the time is between 1min-30min, the drawing temperature is between 300℃-500℃ and the drawing ratio is between 1-10.
[0018] 6) Immerse the filament d obtained in step 5) into a fluororesin nano-dispersion solution with a concentration of 1wt%-20wt% for 1min-30min and then remove it to obtain filament e;
[0019] 7) The filament e obtained in step 6) is dried and heat-treated to obtain an organic-inorganic composite filament. The drying temperature is between 100-200℃ and the drying time is between 1 min-30 min. The heat treatment temperature is between 200-450℃ and the heat treatment time is between 1 min-60 min.
[0020] In this invention, the filament refers to uncut fiber, that is, continuous long fiber, and can therefore also be called long fiber or filament fiber, or simply long fiber. In the above method, the filament in the composite filament obtained in step 7) is a polyimide filament. Unless otherwise specified, in this invention, polyimide fiber is polyimide filament.
[0021] In this invention, the inorganic material is preferably an inorganic oxide, such as TiO2, SiO2, ZrO2, etc., but not limited thereto, and may also be metals such as silver, nickel, and copper, more preferably TiO2.
[0022] In this invention, the inorganic precursor can be transformed into the corresponding inorganic substance through reactions such as ion exchange, hydrolysis, dehydration, and / or reduction. For example, it can be selected from titanium salts such as titanium oxysulfate and tetrabutyl titanate; zirconium salts such as zirconium oxychloride, zirconium nitrate, zirconium sulfate, zirconium propoxide, and zirconium butoxide; silicon salts such as tetraethyl orthosilicate and tetrabutyl orthosilicate, but is not limited thereto. Titanium salts are preferred, and titanium oxysulfate is more preferred.
[0023] In this invention, the fluororesin, also known as fluorocarbon resin, refers to a synthetic polymer compound whose main chain or side chain contains fluorine atoms. For example, it can be selected from polytetrafluoroethylene (PTFE), polychlorotrifluoroethylene (PCTFE), polyvinylidene fluoride (PVDF), ethylene-tetrafluoroethylene copolymer (ETFE), ethylene-chlorotrifluoroethylene copolymer (ECTFE), polyvinyl fluoride (PVF), perfluoroethylene propylene (FEP), etc., but is not limited thereto, and is preferably polytetrafluoroethylene (PTFE).
[0024] It should be noted that, in this invention, the heat treatment temperature in step 7) theoretically results in a better melting effect of the fluoropolymer as the temperature increases, as long as it does not exceed the decomposition temperature.
[0025] In step 1) above, you can choose a type of polyamic acid commonly used in the prior art and use a conventional wet spinning process in the field for spinning. There are no particular limitations. For example, you can refer to the embodiment in Chinese Patent CN102345177B (A high-strength and high-modulus polyimide fiber and its preparation method) for wet spinning.
[0026] In a preferred embodiment of the present invention, in step 2), the inorganic precursor solution is, for example, a 0.6 mol / L TiOSO4 solution;
[0027] In step 3), the immersion time is, for example, 30 minutes;
[0028] In step 4), the fluoropolymer nanodispersion, for example, is a polytetrafluoroethylene (PTFE) nanodispersion (concentration 5 wt%), and is impregnated for 5 min;
[0029] In step 5), for example, drying at 150°C for 15 min, and then stretching twice at 400°C;
[0030] In step 6), for example, immerse in a PTFE nano-dispersion (concentration 5 wt%) for 5 min;
[0031] In step 7), for example, drying at 150°C for 15 min and then heat-treating at 340°C for 60 min, PI / TiO2 / PTFE composite filaments are obtained.
[0032] It should be noted that high-performance fibers such as aramid fiber, aramid III fiber, PBO fiber, PBI fiber, polyarylate fiber, PTFE fiber, carbon fiber, ceramic fiber, and glass fiber can also be formed into organic-inorganic composite fiber filaments by constructing seed points on the fiber surface with inorganic materials through a similar method, then impregnating them with fluororesin emulsion, and then performing high-temperature heat treatment.
[0033] This invention employs an organic / inorganic composite approach to construct a shell layer composed of inorganic materials and fluororesin on the surface of PI fibers, forming an organic / inorganic composite filament consisting of PI-inorganic material-fluororesin. The high modulus of the inorganic materials enhances the compressive strength of the PI fibers, while the excellent self-lubricating properties of the fluororesin improve their wear resistance. Furthermore, the presence of the fluororesin further enhances the adhesion between inorganic materials and PI, and between inorganic materials themselves, resulting in a more uniform and dense coating structure.
[0034] Furthermore, in simple fluororesin coating, if only fluororesin emulsion is used to impregnate PI fibers, the fluororesin adheres to the PI fiber surface in the form of nanoparticles through physical adsorption, resulting in uneven adhesion. The heating method described in CN201810874124.0 reaches a maximum temperature of 200°C, which is insufficient to completely melt the fluororesin, thus failing to form a continuous film layer on the PI fiber surface. Therefore, this invention employs a specific high-temperature treatment temperature to completely melt the fluororesin, thereby enabling the formation of a continuous film layer on the PI fiber surface.
[0035] That is, the key innovation of this invention lies in the formation of an organic / inorganic composite shell on the surface of PI fiber through the combined action of inorganic precursor and fluororesin emulsion; key technical points include the type of inorganic precursor, the type of fluororesin emulsion, and the high-temperature treatment temperature.
[0036] In the polyimide spinning process, polyamic acid (PAA) filaments undergo ion exchange or adsorption with an inorganic precursor solution. Inorganic precursors, such as titanium oxysulfate, tetrabutyl titanate, zirconium oxychloride, zirconium nitrate, zirconium sulfate, zirconium propoxide, zirconium butoxide, tetraethyl orthosilicate, and tetrabutyl orthosilicate, are used to seed the PAA fiber surface as "inorganic precursor seeds." The fiber is then passed through a fluororesin nano-dispersion solution, using the inorganic precursor seeds as a core to improve the uniformity of nanoparticle adsorption on the PAA fiber surface. The fiber is further subjected to drying, hot stretching, secondary impregnation with a fluororesin solution, and heat treatment. During this process, PAA undergoes an imidization reaction to transform into PI; the inorganic precursors undergo dehydration reactions to transform into corresponding inorganic substances, such as TiO2, SiO2, and ZrO2; and the fluororesin nanoparticles melt onto the PI fiber surface to form a continuous and uniform film structure, better bonding the inorganic substances to the PI fiber.
[0037] The organic-inorganic composite filaments provided by this invention can be applied in special protection fields, aerospace fields, etc., to prepare various composite material products, such as radomes, antenna covers, unmanned aerial vehicle shells, flexible airbags, etc. Therefore, this invention also provides a composite material product comprising the organic-inorganic composite filaments of this invention.
[0038] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0039] (1) This invention innovatively develops a method for preparing organic / inorganic composite fiber filaments. It uses inorganic precursors as seed points to improve the adsorption uniformity of fluororesin nanoparticles. Furthermore, under the action of high temperature treatment, it simultaneously completes the transformation of inorganic structure, PI structure, and multi-level physical and chemical structural changes of fluororesin melting to form a continuous film. It utilizes the melting of fluororesin to form a continuous film to improve the adhesion between inorganic materials and PI fibers.
[0040] (2) The above-mentioned technical innovations of the present invention have brought about innovations in the fiber surface structure, forming an organic / inorganic composite filament with PI fiber as the core layer and inorganic material / fluororesin as the shell layer, thereby significantly improving the wear resistance of the fiber, increasing the number of abrasion breaks by two orders of magnitude, and also improving the compressive strength by about 8 to 15% compared with PI filament.
[0041] (3) The inorganic / fluororesin shell in this invention can also effectively reduce the moisture regain of the fiber and improve the aging resistance and atomic oxygen resistance of PI fiber. Attached Figure Description
[0042] Figure 1 SEM images of PI precursor filament, PI / PTFE composite filament, PI / TiO2 composite filament, and PI / TiO2 / PTFE composite filament, where (a) is PI precursor filament; (b) is PI / PTFE composite filament; (c) is PI / TiO2 composite filament; and (d) is PI / TiO2 / PTFE composite filament.
[0043] Figure 2 EDS scan image of PI / TiO2 / PTFE composite filament.
[0044] Figure 3 SEM images of composite filaments after treatment at different temperatures, (a) 190℃, (b) 340℃. Detailed Implementation
[0045] In a preferred embodiment of the present invention, an organic / inorganic composite filament and a method for preparing the same are provided. The preparation method includes the following steps:
[0046] Step 1: Polyamic acid is wet-spun to obtain polyamic acid filaments;
[0047] Step 2: Dissolve inorganic precursors such as Ti salts in water at a concentration of 0.01-2 mol / L to obtain inorganic precursor solutions, such as TiOSO4 solution (0.6 mol / L);
[0048] Step 3: Immerse the polyamic acid filament from Step 1 into the inorganic precursor solution from Step 2 for 1 min to 60 min, then remove it, for example, immerse for 30 min.
[0049] Step 4: Immerse the filaments obtained in Step 3 in a fluoropolymer nanodispersion (concentration 1wt%-20wt%) for 1-30 minutes and then remove them, or immerse them in a polytetrafluoroethylene (PTFE) nanodispersion (concentration 5wt%) for 5 minutes.
[0050] Step 5: The filaments obtained in Step 4 are dried and hot-drawn. The drying temperature is between 100-200℃ and the time is between 1min-30min. The drawing temperature is between 300-500℃ and the drawing ratio is between 1-10. For example, dry at 150℃ for 15min and then draw twice at 400℃.
[0051] Step 6: Immerse the filaments obtained in Step 5 in a fluoropolymer nano-dispersion (concentration 1wt%-20wt%) for 1-30 minutes and then remove them. Alternatively, immerse them in a PTFE nano-dispersion (concentration 5wt%) for 5 minutes.
[0052] Step 7: The filaments obtained in Step 6 are dried (temperature at 100-200℃, time at 1min-30min) and heat-treated (temperature at 200-450℃, time at 1min-60min) to obtain composite fibers. For example, drying at 150℃ for 15min and then heat-treating at 340℃ for 60min will yield PI / TiO2 / PTFE composite filaments.
[0053] The present invention will be further described below with reference to specific embodiments, but the present invention is not limited to the following embodiments. Unless otherwise specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.
[0054] In the description of this specification, references to terms such as "one embodiment," "another embodiment," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment is included in at least one embodiment of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in a suitable manner in any one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of those different embodiments or examples.
[0055] The specific embodiments of the present invention are described in detail below.
[0056] Example 1
[0057] Step 1: Polyamic acid is wet-spun to obtain polyamic acid filaments. For specific implementation, refer to Example 2 in Chinese Patent CN102345177B (A high-strength, high-modulus polyimide fiber and its preparation method);
[0058] Step 2: Dissolve TiOSO4 in water as an inorganic precursor to obtain a TiOSO4 solution (concentration 0.6 mol / L);
[0059] Step 3: Immerse the polyamic acid filament a from Step 1 into the TiOSO4 solution from Step 2 for 30 minutes, then remove it to obtain filament b;
[0060] Step 4: Using polytetrafluoroethylene (PTFE) as a fluororesin, immerse the filament b obtained in step 3 into a PTFE nano-dispersion (concentration 5wt%), and remove it after immersion for 5 minutes to obtain filament c;
[0061] Step 5: Dry the filament c obtained in Step 4 at 150℃ for 15 min, and then draw it twice at 400℃ to obtain filament d;
[0062] Step 6: Immerse the filament d obtained in Step 5 into PTFE nano-dispersion (concentration 5wt%), and remove it after immersion for 5 min to obtain filament e;
[0063] Step 7: Dry the filament e obtained in Step 6 at 150℃ for 15 min, and then heat treat it at 340℃ for 60 min to obtain PI / TiO2 / PTFE composite filament.
[0064] Example 2
[0065] The inorganic precursor in step 2 was replaced with zirconium oxychloride, and the PI / ZrO2 / PTFE composite filament was prepared in the same manner as in Example 1 to obtain the PI / ZrO2 / PTFE composite filament.
[0066] Example 3
[0067] The inorganic precursor in step 2 was replaced with zirconium propoxide, and the PI / ZrO2 / PTFE composite filament was prepared in the same manner as in Example 1 to obtain the PI / ZrO2 / PTFE composite filament.
[0068] Example 4
[0069] The inorganic precursor in step 2 was replaced with tetraethyl orthosilicate, and the PI / SiO2 / PTFE composite filament was prepared in the same manner as in Example 1 to obtain the PI / SiO2 / PTFE composite filament.
[0070] Example 5
[0071] The PTFE nano-dispersion in steps 4 and 6 was replaced with FEP nano-dispersion, and the heat treatment temperature in step 7 was 280°C. Otherwise, the preparation was carried out in the same manner as in Example 1 to obtain PI / TiO2 / FEP composite filaments.
[0072] Comparative Example 1
[0073] The PI precursor fiber without composite treatment was prepared in the same manner as in Example 1, except that steps 1 and 5 and the heat treatment (heat treatment at 340°C for 60 min) in step 7 of Example 1 were used.
[0074] Comparative Example 2
[0075] Steps 2-3 in Example 1 were removed, but otherwise the preparation was carried out in the same manner as in Example 1 to obtain PI / PTFE composite filaments.
[0076] Comparative Example 3
[0077] Steps 4 and 6 in Example 1 were removed, but otherwise the preparation was carried out in the same manner as in Example 1 to obtain PI / TiO2 composite filaments.
[0078] Comparative Example 4
[0079] The heat treatment temperature in step 7 was changed to 190°C, and the PI / TiO2 / PTFE composite filament was prepared in the same manner as in Example 1.
[0080] The filaments obtained from the above embodiments and comparative examples were observed and tested, and the observation and test results are as follows. Figures 1-3 As shown in Table 1.
[0081] Figure 1 SEM images (Hitachi SU8010) of PI precursor filament (Comparative Example 1), PI / PTFE composite filament (Comparative Example 2), PI / TiO2 composite filament (Comparative Example 3), and PI / TiO2 / PTFE composite filament (Example 1) are shown, where (a) is PI precursor filament; (b) is PI / PTFE composite filament; (c) is PI / TiO2 composite filament; and (d) is PI / TiO2 / PTFE composite filament.
[0082] Depend on Figure 1 As can be seen, the PI precursor fiber has a smooth surface and no coating. Figure 1 As can be seen from b, when only PTFE nano-dispersion is used, the PTFE layer aggregates in one area, while other areas are clearly uncoated. This is because the PI fiber surface is smooth and lacks adsorption sites, preventing the PTFE nanoparticles from forming a uniform adsorption on the PI fiber surface. Figure 1 c. It can be seen that even when TiO2 is loaded only on the fiber surface, TiO2 aggregation and uneven surface dispersion still occur. On the other hand, when using the method of the present invention, from Figure 1 As can be seen from d, a uniform island-shaped distribution is formed on the fiber surface, fully demonstrating that under the combined action of TiO2 and PTFE, the effect of promoting uniform PTFE adsorption with TiO2 as the nucleus and forming a uniform and continuous film layer by utilizing the melting effect of PTFE is achieved. Regarding the effect of forming a uniform and continuous film layer, [further details are needed]. Figure 2 The results show the uniform distribution of F and Ti more clearly.
[0083] Figure 2 EDS (Energy Dispersive Spectrometer) scan image of PI / TiO2 / PTFE composite filament (Example 1) (Hitachi SU8010). Figure 2 As can be seen, fluorine and titanium form a uniform distribution on the fiber surface.
[0084] Figure 3 The images are SEM images of the composite filament after heat treatment at different temperatures (a. 190℃, b. 340℃), showing the surface morphology of the composite filament after different heat treatment temperatures in step 7. Figure 3 a, Figure 3 The composite filaments of b are from Comparative Example 4 and Example 1, respectively.
[0085] from Figure 3 As can be seen, when the heat treatment temperature is 190℃, PTFE is still in a particle state and there is no tight bond between them; when the heat treatment temperature reaches 340℃, the particles are fully melted to form a continuous film layer structure.
[0086] The PI precursor, PI / PTFE composite filament, and PI / TiO2 composite filament used in Table 1 below are from Comparative Examples 1 to 3, respectively. The PI / TiO2 / PTFE composite filament used is from Example 1. The abrasion resistance, compression performance, and moisture regain of the above filaments were tested respectively.
[0087] The number of abrasion breaks of the filaments was tested using a yarn-to-yarn abrasion tester (a self-made device by Jiangsu Xiannuo New Material Technology Co., Ltd.), and the results are shown in Table 1. Table 1 shows that the PI raw filament only broke 28 times, the PI / PTFE composite filament reached 2560 times, the PI / TiO2 composite filament reached 86 times, while the composite filament in the example achieved 3170–3540 times, which is two orders of magnitude higher than the raw filament.
[0088] The compressive strength of the monofilament was obtained by the tensile rebound method. The tensile rebound method involves fixing both ends of the monofilament and applying a preload to stretch the fiber. Then, the fiber is cut in the middle, causing it to break and rebound. Under the influence of the rebound force and the fixed point, the monofilament will collapse. The collapse of the upper and lower sections of the fiber is observed under a microscope. The applied preload is the rebound force that causes the fiber to collapse, and the ratio of this value to the fiber cross-sectional area can be considered the compressive strength of the upper or lower section of the fiber. The test results are shown in Table 1. Table 1 shows that the compressive strength of the PI precursor is approximately 340 MPa, while the compressive strength of the composite filament in the example can reach 368 MPa to 392 MPa, an increase of approximately 8% to 15%.
[0089] In addition, the moisture regain of the fibers was tested according to GB / T6503-2017 "Test Method for Moisture Regain of Chemical Fibers", and the results are shown in Table 1. Table 1 shows that the moisture regain of the PI precursor filament was 1.11%, while the moisture regain of the composite filament in the examples could reach 0.44% to 0.49%, a reduction of approximately 55% to 60%.
[0090] Table 1. Abrasion resistance, compression properties, and moisture regain of filaments
[0091]
[0092]
[0093] The results above demonstrate that the organic-inorganic composite filament preparation process described in this invention can significantly improve the compression resistance and abrasion resistance of PI fibers. Consequently, the prepared filaments exhibit superior compression resistance and abrasion resistance. Furthermore, it can effectively reduce the moisture regain of the fibers. In addition, due to the continuous shell formed by the inorganic material and fluororesin covering the surface, the aging resistance and atomic oxygen resistance of the PI fibers may also be improved.
[0094] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A method for preparing organic-inorganic composite filaments, characterized in that, Includes the following steps: 1) Polyamic acid is wet-spun to obtain polyamic acid filament a; 2) Dissolve the inorganic precursor in water to obtain an inorganic precursor solution with a concentration of 0.01 mol / L-2 mol / L, wherein the inorganic precursor is one or more selected from titanium salts, zirconium salts, and silicon salts; 3) Immerse the filament a obtained in step 1) into the inorganic precursor solution in step 2) for 1 min to 60 min, and then take it out to obtain polyamic acid filament b; 4) Immerse the filament b obtained in step 3) in a fluororesin nano-dispersion solution with a concentration of 1wt%-20wt% for 1min-30min and then take it out to obtain filament c; 5) The filament c obtained in step 4) is dried and hot-drawn to obtain filament d, wherein the drying temperature is between 100-200℃ and the time is between 1min-30min, the drawing temperature is between 300℃-500℃ and the drawing ratio is between 1-10. 6) Immerse the filament d obtained in step 5) into a fluororesin nano-dispersion solution with a concentration of 1wt%-20wt% for 1min-30min and then remove it to obtain filament e; 7) The filament e obtained in step 6) is dried and heat-treated to obtain an organic-inorganic composite filament. The drying temperature is between 100-200℃ and the drying time is between 1min-30min. The heat treatment temperature is between 280-450℃ and the heat treatment time is between 1min-60min.
2. The preparation method according to claim 1, wherein, The fluororesin is selected from one or more of polytetrafluoroethylene (PTFE), polychlorotrifluoroethylene (PCTFE), polyvinylidene fluoride (PVDF), ethylene-tetrafluoroethylene copolymer (ETFE), ethylene-chlorotrifluoroethylene copolymer (ECTFE), polyvinyl fluoride (PVF), and perfluoroethylene propylene (FEP).
3. The preparation method according to claim 1, wherein, The titanium salt is selected from titanium oxysulfate and tetrabutyl titanate; the zirconium salt is selected from zirconium oxychloride, zirconium nitrate, zirconium sulfate, zirconium propoxide, and zirconium butoxide; the silicon salt is selected from tetraethyl orthosilicate and tetrabutyl orthosilicate.
4. The preparation method according to claim 1, wherein, In step 2), the inorganic precursor solution is a 0.6 mol / L TiOSO4 solution; and / or In step 3), the immersion time is 30 minutes; and / or In step 4), the fluoropolymer nanodispersion is a 5wt% polytetrafluoroethylene nanodispersion, and the impregnation is carried out for 5 min; and / or In step 5), dry at 150°C for 15 min, then stretch twice at 400°C; and / or In step 6), immerse in a 5 wt% polytetrafluoroethylene nanodispersion for 5 min; and / or In step 7), the PI / TiO2 / PTFE composite filament is dried at 150°C for 15 min and then heat-treated at 340°C for 60 min to obtain the PI / TiO2 / PTFE composite filament.
5. An organic-inorganic composite filament, characterized in that, The organic-inorganic composite filament is prepared by the preparation method according to any one of claims 1 to 4. The organic-inorganic composite filament comprises a filament and a shell layer formed on the surface of the filament. The shell layer is an organic-inorganic composite shell layer composed of inorganic substances and fluororesin, and the fluororesin forms a continuous film layer on the surface of the filament. Compared with the filament, the organic-inorganic composite filament can simultaneously improve the compression resistance and wear resistance.
6. The organic-inorganic composite filament according to claim 5, wherein, The organic-inorganic composite filament is a polyimide fiber.
7. The organic-inorganic composite filament according to claim 5, wherein, The fluororesin is selected from one or more of polytetrafluoroethylene (PTFE), polychlorotrifluoroethylene (PCTFE), polyvinylidene fluoride (PVDF), ethylene-tetrafluoroethylene copolymer (ETFE), ethylene-chlorotrifluoroethylene copolymer (ECTFE), polyvinyl fluoride (PVF), and perfluoroethylene propylene (FEP).
8. The organic-inorganic composite filament according to claim 5, wherein, The inorganic material is one or more selected from TiO2, SiO2, and ZrO2.
9. A composite material article comprising an organic-inorganic composite filament prepared by any one of claims 1 to 4 or an organic-inorganic composite filament prepared by any one of claims 5 to 8.
Citation Information
Patent Citations
High-strength high modulus polyimide fiber and preparation method thereof
CN102345177B
High-strength wear-resistant type polyimide-fiber rope belt and preparation method thereof
CN108950854A
A polyimide fiber surface modification method and application thereof
CN115787288B
Polyimide fiber and preparation method thereof
CN115819764A
Corona-resistant polyimide composite thin film and preparation method thereof
CN109293966A